(untitled) (Journal of Management and Social Sciences, 2016)
Performance Management System is said to have been developed and implemented resulting in the failure to deliver the results people expect from it. The main objective of the paper is to examine the effect of Performance Management System (PMS) on Employees’ Attitude in the Nigerian Banking Sector. Stratified Sampling Technique were used to select a total number of 180 staff from Head Offices of the 15 listed Banks in Nigerian Stock Exchange (NSE). Primary data were collected using a structured questionnaire. Data obtained were analysed and presented using both descriptive and inferential statistics. Correlation and regression analysis were used to test the hypotheses formulated for the study. The findings revealed that R 2 of 0.2177, 0.4066 and 0.6687 values suggested that variables in the model are all jointly significantly influence the probability of the Nigerian banking sector performing better. The study concluded that the implementation of PMS is said to be the commencement of changed attitude to work due to continuous and systematic assessment of employees’ performance on a regular basis. The study recommended that; management should continue to communicate the importance of Performance Management System (PMS) to employees until the process is entrenched. Keywords Performance management, performance management system, employees, attitude, Nigerian banking sector, performance indicator